Diskriminasi Pemenuhan Hak Sipil Bagi Penganut Agama Lokal - Sukirno Sukirno (Administrative Law Department, Faculty of Law, Universitas Diponegoro, 2018)
AbstractThis paper is the result of research to explore whether the guarantee of religious freedom as guaranteed by Article 29 paragraph (2) of the 1945 Constitution of the Republic of Indonesia applies to adherents of local religions or beliefs, especially indigenous peoples and their implications for population document services. The location of the first year research was carried out on indigenous peoples in Java, namely the Sunda Wiwitan and Adam Religion from Sedulur Sikep / Samin. Then in the second year, there was research outside Java, namely followers of the Parmalim religion in Laguboti, North Sumatra. The results showed that there were different treatments for indigenous people who were still purely embracing local religions and those who embraced local religions who had converted to one of the recognized religions of the state. For indigenous people who have switched to embrace one of the religions recognized by the state, they are not discriminated against by the state, meaning that they can easily obtain residence documents. Whereas for the indigenous people who continue to embrace the local religion get discriminatory treatment, namely on their Identity (KTP) wrote a column of non-religious beliefs as decided by the Constitutional Court No. No.97 / PUU-XIV / 2016, it is difficult to obtain a marriage certificate, the birth certificate is not as usual, because the marriage of his parents has not been recorded.Keywords: Discrimination, Civil Rights, Population Documents, Local Religion.AbstrakTulisan ini merupakan hasil penelitian untuk menggali apakah benar jaminan kebebasan beragama itu sebagaimana dijamin Pasal 29 ayat (2) UUD NRI 1945 berlaku bagi penganut agama lokal atau kepercayaan, khususnya masyarakat adat dan implikasinya terhadap layanan dokumen kependudukan. Lokasi penelitian tahun pertama telah dilakukan pada masyarakat adat di Jawa, yaitu pada masyarakat penganut Sunda Wiwitan dan Agama Adam dari Sedulur Sikep/Samin. Kemudian pada tahun kedua telah dilakukan penelitian di luar Jawa, yaitu penganut agama Parmalim di Laguboti, Sumatera Utara. Hasil penelitian menunjukkan, ada perlakuan yang berbeda bagi masyarakat adat yang masih murni memeluk agama lokal dan masyarakat pemeluk agama lokal yang sudah beralih memeluk salah satu agama yang diakui oleh negara. Bagi masyarakat adat yang sudah beralih memeluk salah satu agama yang diakui oleh negara tidak diperlakukan diskriminatif oleh negara, artinya mereka dapat dengan mudah memperoleh dokumen kependudukan. Sedangkan bagi masyarakat adat yang tetap memeluk agama lokal mendapatkan perlakuan diskriminatif, yaitu di KTP mereka tertulis kolom kepercayaan bukan agama seperti yang diputuskan oleh Mahkamah Konstitusi No. No.97/PUU-XIV/2016, sulit mendapatkan akta perkawinan, akta kelahiran tidak sebagaimana umumnya, karena perkawinan orang tuanya belum dicatatkan.Kata Kunci: Diskrininasi, Hak Sipil, Dokumen Kependudukan, Agama Lokal.